Simulation and Experimental Study of A Hybrid System for Different Loads - Bayrak, Zehra Ural; Gencoglu, Muhsin Tunay (Ieee, 2014)
In recent years, renewable energy sources such as solar, hydrogen, wind and so on are becoming more popular with the global warming and depletion of fossil fuels. Especially, hydrogen and solar energy have been used in hybrid system to meet these needs. Solar cells generate electricity depending on weather conditions. Therefore, the fuel cells which convert chemical energy of a reaction directly into the electrical energy used in conjunction with solar cells. In this way, energy demand can be supplied using clean energy sources without interruption. In this study, simulation and experimental studies of the solar cell and fuel cell hybrid system have been performed. 100 W fuel cell and 160 W solar cell have been employed in the experimental study. The energy demand is provided from solar cell when the sun is sufficient. During overnight and sunlight is insufficient, interrupted power is provided by the fuel cell. 40 W incandescent lamp and fan (inductive load) were used as the load. The output voltage of the fuel cell and buck converter are given for the experimental results. The curves of load current and voltage were obtained using LabVIEW interface. To compare the experimental and simulation results, same curves were obtained from the simulation.
3rd THE INTERNATIONAL CONFERENCE on RENEWABLE ENERGY RESEARCH and APPLICATIONS (ICRERA) -- OCT 19-22, 2014 -- Milwakuee, WI
Keywords: fuel cell; solar cell; hybrid system; simulation